Plasma Inflammatory Factors Are Associated with Anxiety, Depression, and Cognitive Problems in Adults with and without Methamphetamine Dependence: An Exploratory Protein Array Study - Huckans, Marilyn; Fuller, Bret E.; Chalker, Alison L. N.; Adams, Madeleine; Loftis, Jennifer M. (Frontiers in Psychiatry, 2015)
Objectives: It is hypothesized that immune factors influence addictive behaviors and contribute to relapse. The primary study objectives were to: 1) compare neuropsychiatric symptoms across adults with active methamphetamine dependence, in early remission from methamphetamine dependence, and with no history of substance dependence, 2) determine whether active or recent methamphetamine dependence affects the expression of immune factors, and 3) evaluate the association between immune factor levels and neuropsychiatric symptoms. Methods: A cross-sectional study was conducted using between group comparisons and regression analyses to investigate associations among variables. Eighty-four adults were recruited into control (n = 31), methamphetamine (MA)-active (n = 17), or MA-remission (n = 36) groups. Participants completed self-report measures of anxiety, depression, and memory complaints and objective tests of attention and executive function. Blood samples were collected, and a panel of immune factors was measured using multiplex technology. Results: Relative to controls, MA dependent adults evidenced greater anxiety and depression during active use (p < 0.001) and remission (p < 0.007), and more attention, memory, and executive problems during remission (p < 0.01) but not active dependence. Regression analyses identified 10 immune factors (putatively associated with cytokine-cytokine receptor interactions) associated with anxiety, depression, and memory problems. Conclusion: While psychiatric symptoms are present during active methamphetamine dependence and remission, at least some cognitive difficulties emerge only during remission. Altered expression of a network of immune factors contributes to neuropsychiatric symptom severity.